A Summary of the Literature Evaluating Adherence and Persistence with Oral Anticoagulants in Atrial Fibrillation - Obamiro, K.; Stafford, Leanne; Bereznicki, L. (Adis International Ltd., 2016)
© 2016, Springer International Publishing Switzerland.Atrial fibrillation (AF) is a growing public health concern and remains an independent risk factor for ischemic stroke. Warfarin, a commonly used oral anticoagulant, is associated with a 60–70 % relative reduction in stroke risk and a reduction in mortality of 26 %. However, warfarin has several limitations, including a narrow therapeutic window, variable dose response, multiple interactions with other drugs and concurrent illnesses, and the need for frequent laboratory monitoring. In recent years, the direct acting oral anticoagulants (DOACs), including dabigatran, rivaroxaban, apixaban and edoxaban, have been developed to overcome the limitations of warfarin therapy. These treatment strategies are either comparable or superior to warfarin in stroke prevention in AF. Despite the documented effectiveness of oral anticoagulants in AF, patients may not derive optimal benefit if they fail to adhere or fail to continue with their medication. This may lead to treatment failure, increased hospitalization and mortality. This review summarizes the literature regarding adherence and persistence (or discontinuation) rates with oral anticoagulants in the management of AF; the impact of non-adherence and non-persistence on treatment outcomes; and the effectiveness of strategies to improve adherence and persistence with oral anticoagulant therapy.